The Composition and style of the story 百鬼夜行街 (‘A Hundred Ghosts Parade Tonight’) - Пихтовникова, Лидия Сергеевна; Мотрохов, Александр Иванович (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2019)
by Xia Jia. The article deals with the composition of the story ‘百鬼夜行街 by the Chinese writer Xia Jia. The composition of the text / speech product has been considered in the paper as an integral component of the style (E. Riesel). The idea of the speech product composition in a linguistic perspective is based on a four-level hierarchical structure of the composition, each level being preparatory for the higher ones. The components of each level and their specific content in the story have been described. On the formal-content level of the composition, typical for а story compositional speech forms and an architectonic speech form ‘dialogue’ have been considered; their role in the plot has been explained.On the content level of the composition, plotlines leading to the climax have been studied, and allocation of compositional speech forms along the main line has been stated. Both on the same level and figurative-conceptual level (L.S. Pikhtovnikova), formation of the opposite concepts ALIVE CHILD / CHOSTS and appearance of contradictory attributes of this concepts have been shown. The text analysis of the story ‘The Ghosts street’ by Xia Jia demonstrates the peculiarity of all compositional levels filling with sense. However, the compositional structure itself, types of compositional and architectonic speech forms, and text division remain conventional as well as in other speech products.The prospects for this work are enhanced composition study of other works by Xia Jia, including the conceptual level analysis on the basis of extraction and description of other key concepts; further detection of the link between composition and stylistics, and this author’s idiostyle; application of the developed approach to the research of compositional and stylistic features of other famous Chinese writers’ works.